A128 ATYPICAL VENOUS THROMBOEMBOLISM IN INFLAMMATORY BOWEL DISEASE: A CASE SERIES OF 2 LIFE-THREATENING PRESENTATIONS. (15th March 2019) - Chan, M; Reinglas, J; Lu, K; Murthy, S
Abstract: Background: Patients with inflammatory bowel disease (IBD) carry a 2–4 fold higher risk of venous thromboembolism (VTE) than persons in the general population. Most VTE present as deep vein thrombosis (DVT) of the lower extremity or as pulmonary emboli (PE), but they can also occur in other locations, including mesenteric and cerebral sinus thrombosis. Such atypical VTE may evade detection until the development of serious complications. Aims: We describe 2 unusual presentations of VTE associated with serious sequalae at our centre and review the literature of VTE in IBD. Methods: We retrospectively reviewed 2 atypical cases of VTE in IBD patients admitted to The Ottawa Hospital in June 2018. We also conducted a Pubmed search to review the literature regarding the incidence and varied manifestations of VTE in persons with IBD. Results: A 21-year old male with a history of ulcerative colitis presented with typical symptoms of a colitis flare with pain and diarrhea along with severe unremitting abdominal pain. A flexible sigmoidoscopy showed severe ulcerative colitis and an area of ischemic colitis in the sigmoid colon. Symptoms did not improve with IV steroids and a CT scan was done showing extensive abdominal mesenteric venous thrombosis that was treated with systemic anticoagulation and close monitoring. A 58-year old female with a history of ALS and colitis, was found to have severe ulcerative colitis on endoscopy. She developed a severe headache followed by unilateral parasthesias and weakness and found to have a cerebral sinus venous thrombosis. This was complicated by a parietal lobe haemorrhagic infarction and death. IBD in itself is a risk factor for VTE, but the risk increases further with active disease, hospitalization, steroid use and surgery. The use of immunomodulators and biologic agents has been found to decrease the risk of VTE. Mesenteric and cerebral venous thrombosis make up <10% of VTE complications in IBD. Conclusions: While VTE in IBD patients is not rare, atypical presentations, such as mesenteric and cerebral sinus thrombosis, are less common and may evade diagnosis until the development of serious sequelae. Clinicians should be vigilant about recognizing the varied presentations of VTE in the IBD population. All IBD patients admitted to hospital should receive VTE prophylaxis, as per current guidelines. Funding Agencies: None